Editorial: Training in Teaching Innovation. Engineering 2030 - Elena Cano García; Beatriz Amante García; María Martínez Martínez (Journal of Technology and Science Education, 2022)
This issue includes the best works, the result of the teaching innovation conferences that were held for the closing of the training program “Training in Teaching Innovation. Engineering 2030” given by the University of Barcelona for professors of engineering degrees from the Catholic University of Northern Chile and the University of Antofagasta (sponsored by HEUMA CORFO and the team of trainers included professors from the Universitat Politècnica de Catalunya, professors at the Open University of Catalonia and faculty of the University of Barcelona, which is the program's coordinating institution) and which were held at the end of March 2021.